2016
DOI: 10.1111/cch.12367
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in children with myelomeningocele: a systematic review of the literature

Abstract: Myelomeningocele (MMC) is the most complex congenital birth defect compatible with life. To provide the best health care for children with MMC, clinicians and researchers have to understand health and functional status of their patients as well as factors influencing their quality of life (QOL). The objective is to review studies that assess health-related quality of life (HRQOL) and determinants of HRQOL in children with MMC. The data sources include MEDLINE, along with reference lists of relevant reviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…Along with physical domains, a number of additional factors were associated with lower HRQOL scores; the investigation and understanding of these factors as a basis to develop interventions designed to improve QOL emerged as an important pursuit. Consistent with previous reviews of HRQOL in patients with SB [26,48], our findings demonstrated that most studies were cross-sectional in nature and described varying degrees of HRQOL divergence on parent and selfreported scores related to emotional, social, and school domains (Table 1). Moreover, a generic measure of QOL was utilized by the majority of studies (n = 15/18; 83%), of which two were supplemented with the use of the SB-HRQOL [43,44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Along with physical domains, a number of additional factors were associated with lower HRQOL scores; the investigation and understanding of these factors as a basis to develop interventions designed to improve QOL emerged as an important pursuit. Consistent with previous reviews of HRQOL in patients with SB [26,48], our findings demonstrated that most studies were cross-sectional in nature and described varying degrees of HRQOL divergence on parent and selfreported scores related to emotional, social, and school domains (Table 1). Moreover, a generic measure of QOL was utilized by the majority of studies (n = 15/18; 83%), of which two were supplemented with the use of the SB-HRQOL [43,44].…”
Section: Discussionsupporting
confidence: 90%
“…In the US, 25% of children live in immigrant families [23], and of the estimated 55 million Hispanics/Latinos, nearly three of every four speaks Spanish at home while remaining the fastest-growing demographic group [24,25]. In this setting, previous systematic reviews of health-related QOL (HRQOL) assessments have called for the exploration of social environments and HRQOL [26]. We sought to examine if appropriately validated instruments, which take into account cultural context, are available and the extent of their use to assess QOL in this historically underserved US population.…”
Section: Introductionmentioning
confidence: 99%
“…Neural tube defects (NTDs) are a group of severe congenital disorders associated with substantial mortality, morbidity, long‐term disability, and psychological and economic costs . Many NTDs are preventable with folic acid, and long‐term survival and quality of life among those living with NTDs can be improved through access to appropriate clinical care and rehabilitative services . However, efforts for primary prevention and addressing the needs of those living with NTD have been hampered by a lack of transparent prevalence estimates to quantify the burden, especially in resource‐poor settings.…”
Section: Introductionmentioning
confidence: 99%
“…Anencephaly, failed closure of the anterior neuropore, and spina bifida, failed closure of the posterior neuropore, are the two most common NTDs. While nearly all babies affected by anencephaly die in utero or shortly after birth, those affected by spina bifida typically survive, but endure mild to severe intellectual, neurologic, and/or physical disabilities throughout their lives . The emotional and financial burden of such birth defects is often overwhelming, with average management costs for this lifelong defect exceeding $700 000 per patient…”
Section: Introductionmentioning
confidence: 99%